Evaluating the perceived value of forensic accounting: a systematic review method - Nourhene Guellim; Nafisah Yami; Abdelrazaq Farah Freihat; Hashem Alshurafat; Majdi Wael Alkababji; Mohammed Alzahrane; Walaa Nasr-El-dein Gad; Mohamed Shaaban Ibrahim shaaban; Rana Mahmoud Abdou Mostafa (Discover Sustainability, 2024)
Abstract This research systematically reviews existing literature to evaluate the perceived value of forensic accounting. The review examines the evolution of forensic accounting, key services provided, necessary skills, professional standards, and educational requirements. It also addresses the expectation gap in forensic accounting education and identifies areas for future research. By synthesizing data from various studies, the paper presents a comprehensive overview of the current state of forensic accounting research. Key findings indicate a growing global demand for forensic accounting, evidenced by the establishment of specialized units within major firms and regional accounting entities. The review concludes with insights into the general characteristics and classification schemes of forensic accounting studies, offering a detailed examination of the field’s present and future directions.